Adjustment policies and development strategies in the Arab world - El-Naggar, Saʻid; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This volume comprises papers presented at a seminar held in Abu Dhabi, United Arab Emirates, February 16-18, 1987, and organized by the International Monetary Fund and the Arab Monetary Fund.
Papers presented at a seminar held in Abu Dhabi, United Arab Emirates, February 16-18, 1987.
Includes bibliographical references.
lje 26/09/2018
Loans
Keywords: Economic development; Economic policy; Economic conditions; Arab countries